Numerical analysis on chaos attractors using a backward difference formulation - Rasedee, A. F. N.; Abdul Sathar, M. H.; Mohd Najib, N.; Wong, T. J.; Koo, L. F. (Lviv Polytechnic National University, 2022)
The chaos attractor is a system of ordinary differential equations which is known for having chaotic solutions for certain parameter values and an initial condition. Research conducted in the current work establishes a backward difference algorithm to study these chaos attractors. Different types of chaos mapping, namely the Lorenz chaos, 'sandwich' chaos and 'horseshoe' chaos will be analyzed. Compared to other numerical methods, the proposed backward difference algorithm will show to be an efficient tool for analyzing solutions for the chaos attractors.